Development of barley and yeast β-glucan aerogels for drug delivery by supercritical fluids - Salgado, Marta (2017)
Polysaccharide aerogels are a good alternative as carriers for drug delivery, since they allow high loading of the active compounds in matrices that are non-toxic, biocompatible and from a renewable feedstock. In this work, barley and yeast β-glucans aerogels were produced by gelation in aqueous solution, followed by solvent exchange and drying with supercritical CO2. First, viscoelastic properties and melting profile of the hydrogels were determined. Then, the obtained aerogels were analyzed regarding morphology, mechanical properties and behavior in physiological fluid. Both in the hydrogels and in the aerogels, big differences were observed between barley and yeast β-glucans due to their different chain structure and gelation behavior. Finally, impregnation of acetylsalicylic acid was performed at the same time as the drying of the alcogels with supercritical CO2. The release profile of the drug in PBS was analyzed in order to determine the mechanism governing the release from the β-glucan matrix.